Pelatihan Toeic sebagai Upaya Pengembangan Profesional Pada Peserta Didik SMK Negeri Dander Bojonegoro - Yuniarta Ita Purnama; Chyntia Heru Woro Prastiwi; Meiga Ratih Tirtanawati; Refi Ranto Rozak (IKIP PGRI Bojonegoro, 2019)
TOEIC as the medium of the students’ professional development at Vacational High School. This article aimed at describing how to empower English-literacy culture through TOEIC training to the graders XII TKR 3, XII TGB 2, and XII TBSM 2 of State Vacational High School Dander Bojonegoro. The TOEIC training given including listening and reading skill. The result of this Community Service Program showed that the score of TOEIC training is low because of the students of State Vacational High School Dander Bojonegoro have not mastered TOEIC test. They did not know and understand about TOEIC. There is not TOEIC simulation yet. The student English background, especially on vocabulary mastery is still low. There were 81 students joined the TOEIC test. 26 students from the twelveth grade of TKR 3. 26 students from the twelveth grade of TGB 2. and 29 students from the twelveth grade of TBSM 2. The highest of TOEIC score is 64 and the lowest of TOEIC score is 8. The highest of mean score is reach by TGB 2 grade with 32 score, and the lowest of mean score is is reach by TBSM 2 with 29 score. So, it is necessary to conduct another TOEIC training for students of State Vacational High School Dander Bojonegoro So, what’s is your recommendation? Solution?Keywords: GLS, , TOEIC, Vacational High School ABSTRAKTOEIC merupakan sarana pengembangan profesional peserta didik pada Sekolah Menengah Kejuruan. Artikel ini bertujuan menggambarkan bagaimana memberdayakan budaya literasi Bahasa Inggris melalui pelatihan TOEIC pada peserta didik kelas XII TKR 3, XII TGB 2, XII TBSM 2 SMK Negeri Dander Bojonegoro. Pelatihan TOEIC yang diberikan meliputi ketrampilan mendengar dan membaca. Hasil PKM ini menunjukkan bahwa hasil skor pelatihan TOEIC masih jauh dari sempurna dikarenakan peserta didik SMKN Dander belum terlatih/terbiasa dan belum menguasai soal soal TOEIC. Mereka belum begitu mengenal dan paham tentang TOEIC serta belum pernah ada simulasi atau pelatihan TOEIC yang diadakan di sekolah sebelumya. Selain itu latar belakang Bahasa Inggris terutama pada kosakata yang berhubungan dengan jurusan yang mereka pelajari masih lemah. Terdapat 81 peserta didik yang melaksanakan tes TOEIC, 26 peserta didik jurusan TKR 3, 26 peserta didik jurusan TGB 2 dan 29 peserta didik jurusan TBSM 2. Hasil nilai simulasi TOEFL tertinggi adalah 64 dan nilai terendah adalah 8. Nilai rata rata tertinggi diraih oleh kelas TGB 2 dengan jumlah 32, dan nilai rata rata terendah dengan jumlah 29 ada di kelas TBSM 2. Oleh karena itu, perludiadakan pelatihan TOEIC lagi bagi peserta didik SMK Negeri Dander Bojonegoro.